2019
DOI: 10.1111/age.12776
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure in multiple Chinese goat populations using a SNP panel

Abstract: SummaryInformation about genetic diversity and population structure among goat breeds is essential for genetic improvement, understanding of environmental adaptation as well as utilization and conservation of goat breeds. Here, we measured genetic diversity and population structure in multiple Chinese goat populations, namely, Nanjiang, Qinggeda, Arbas Cashmere, Jining Grey, Luoping Yellow and Guangfeng goats. A total of 193 individuals were genotyped for about 47 401 autosomal single nucleotide polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 30 publications
9
10
1
Order By: Relevance
“…Therefore, it is useful to consider our results in the context of the demographic history of the goat population in China. This finding is consistent with our previous study of genetic diversity and population structure, in which it was discussed that the principal component and admixture analysis clearly clustered the population corresponding to their geographic distribution and genetic construction [25]. Comparatively, a decreasing recent Ne was observed for the AC and GF breeds, and their estimated values were closer to 64 and 95 at 13 generations ago, suggesting that these animals were strongly affected by selection pressure or genetic drift which resulted in population decline [44].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, it is useful to consider our results in the context of the demographic history of the goat population in China. This finding is consistent with our previous study of genetic diversity and population structure, in which it was discussed that the principal component and admixture analysis clearly clustered the population corresponding to their geographic distribution and genetic construction [25]. Comparatively, a decreasing recent Ne was observed for the AC and GF breeds, and their estimated values were closer to 64 and 95 at 13 generations ago, suggesting that these animals were strongly affected by selection pressure or genetic drift which resulted in population decline [44].…”
Section: Discussionsupporting
confidence: 93%
“…In our previous study, we revealed the genetic diversity and population structure of goat populations [25]. Considering this fact, here, we estimated genome-wide linkage disequilibrium and the extent of effective population size in six Chinese goat populations using a 50K SNP panel.…”
Section: Discussionmentioning
confidence: 99%
“…This is caused by the differences among breeds, mating schemes, and breed plans. The F -statistic in this population is very low, which is far lower than that reported in other studies ( 37 , 40 ). This indirectly reflects the genetic differentiation among the population.…”
Section: Discussioncontrasting
confidence: 81%
“…Recently, the availability of a medium-density single nucleotide polymorphisms (SNP) panel (8) enabled goat genomic studies at a level of resolution that was not possible with previously used markers, such as microsatellites. Several studies have already used this new SNP array tool to analyze the genetic diversity and population structure of local goat breeds or populations within countries in relation to other cosmopolitan breeds, such as in Italy (9), France (10), Switzerland (11), Spain (12), Pakistan (13), China (14), Canada, and Australia (15). Since the International Goat Genome Consortium (IGGC, http://www.goatgenome.org) was created in 2012, the range of genomic tools and publicly available information for goats has increased immensely (16).…”
Section: Introductionmentioning
confidence: 99%